Implementation of Intelligent Parking System Using IoT-Based Devices (case Study of Galaxy Mall Surabaya) - Weka Sadya Wasana; R. Dimas Adityo; Wiwiet Herulambang (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
Many parking spaces available today generally require drivers to find their own location empty parking. Especially in parking lots located in large areas such as the Galaxy Mall area Surabaya. This will cause problems getting parking location information because drivers are not uncommon have to circle the parking building to get an empty parking location. The problem can avoided if the driver already knows the state of the parking location in the area to be seven. Driver can find out the availability of vacant parking locations in the destination area. In this case, we need a a system that can help drivers find vacant parking locations. Internet of things is a a concept or program by which an object has the ability to transmit or transmit data through the network without using the help of computers and humans. Internet of things or often called IoT is currently experiencing many developments. From the test results it can be concluded that the average Raspberry Pi boot delay on this system is 221.1 seconds. Sensor, From the test results it can be concluded that the average delay in scanning the QR Code using a Raspberry Pi camera at the entrance bar is 59.3 seconds, From the test results it can be concluded that the average delay in scanning QR Code using a camera The Raspberry Pi on the exit bar is 59.4 seconds